Treating and avoiding herpes and tinea infections in contact sports - Landry, G. L.; Chang, C. J.; Mees, P. D.; Harmon, K. G.; Rubin, A. (The Physician and Sportsmedicine, 2004)
Sports that require skin-to-skin contact between competitors, such as wrestling, create environments where infections can spread. Skin screening checks are made before any wrestling competition, but this usually doesn't happen with other sports. Two of the most common skin infections are herpes gladiatorum (caused by the same virus that causes cold sores) and tinea gladiatorum, also known as ringworm (caused by a fungus). These skin infections can spread rapidly among teammates, coaches, and opponents, so it is very important to treat the infection as soon as it is discovered. Athletes who have active skin infections can be disqualified from competition and withheld from practice. The following questions were answeres for athletes: - How do I know it's not just an ordinary rash? - What should I do if I notice a skin outbreak that might be herpes or tinea? - How can I avoid catching a skin disease from another player? - Will I be disqualified from play? - I had a rash and it went away, but now it keeps coming back. Can I prevent it?